2007
DOI: 10.1213/01.ane.0000284670.17412.b6
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Peripheral Nerve Blockade for Inpatient and Outpatient Postoperative Analgesia in Children

Abstract: It is feasible to implement a CPNB program to provide an alternative method of inpatient and outpatient postoperative analgesia after orthopedic surgery in children when appropriate expertise is available. Patient and family education along with frequent follow-up are crucial to detect and address adverse events promptly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 28 publications
4
81
0
Order By: Relevance
“…Postoperative analgesia was excellent. As demonstrated in other studies, [4][5][6]11 CPNB provided a high level of satisfaction in postoperative pain management in our pediatric patients. Nevertheless, we did not compare CPNB with other methods of postoperative analgesia.…”
Section: Quality Of Postoperative Analgesiasupporting
confidence: 82%
See 4 more Smart Citations
“…Postoperative analgesia was excellent. As demonstrated in other studies, [4][5][6]11 CPNB provided a high level of satisfaction in postoperative pain management in our pediatric patients. Nevertheless, we did not compare CPNB with other methods of postoperative analgesia.…”
Section: Quality Of Postoperative Analgesiasupporting
confidence: 82%
“…The incidence of PONV in our trial is similar to the results noted by Ganesh et al (14%). 6 The results of these two studies are lower than those of continuous pediatric epidural analgesia trials, which reported an incidence of PONV from 22 to 40%. [22][23][24] The authors claimed that nausea and vomiting were related to epidural opioid use.…”
Section: Adverse Eventsmentioning
confidence: 74%
See 3 more Smart Citations